Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/srep13723
|View full text |Cite
|
Sign up to set email alerts
|

Links between fear of humans, stress and survival support a non-random distribution of birds among urban and rural habitats

Abstract: Urban endocrine ecology aims to understand how organisms cope with new sources of stress and maintain allostatic load to thrive in an increasingly urbanized world. Recent research efforts have yielded controversial results based on short-term measures of stress, without exploring its fitness effects. We measured feather corticosterone (CORTf, reflecting the duration and amplitude of glucocorticoid secretion over several weeks) and subsequent annual survival in urban and rural burrowing owls. This species shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 51 publications
2
78
1
Order By: Relevance
“…Previous studies have shown enhanced annual survival in urban adult birds, in particular because of higher resource availability over winter (Rebolo-Ifran et al, 2015;Marzluff et al, 2016). In the context of the pace-of-life theory, such decreased probability of mortality would be indicative of a slower pace-of-life (Réale et al, 2010).…”
Section: Perspectives On a Multivariate Long-term Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown enhanced annual survival in urban adult birds, in particular because of higher resource availability over winter (Rebolo-Ifran et al, 2015;Marzluff et al, 2016). In the context of the pace-of-life theory, such decreased probability of mortality would be indicative of a slower pace-of-life (Réale et al, 2010).…”
Section: Perspectives On a Multivariate Long-term Processmentioning
confidence: 99%
“…Urban birds are usually more aggressive (e.g., Minias, 2015;Davies and Sewall, 2016), bolder (e.g., Ducatez et al, 2017), can be approached more closely by humans (e.g., Lin et al, 2012;Møller et al, 2015), are less neophobic (e.g., Tryjanowski et al, 2016), have higher levels of disturbance tolerance (Lowry et al, 2013) and reduced levels of physiological stress response (e.g., Partecke et al, 2006;Minias, 2015). Other empirical comparisons between urban and rural birds have also suggested shifts in breeding strategies: urban birds usually have earlier laying dates, smaller clutch sizes, lower reproductive success (e.g., Peach et al, 2008;review in Chamberlain et al, 2009), and higher adult survival rates (e.g., Rebolo-Ifran et al, 2015). Hence overall, the empirical literature so far seems to suggest that urban birds tend to have slow life histories yet fast behavioral syndromes (Figure 1 in Réale et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we focused on the burrowing owl, a bird species largely studied as a model of recent urban colonization (Carrete and Tella, 2010Rodriguez-Martínez et al, 2014;Rebolo-Ifrán et al, 2015;Carrete et al, 2016). We experimentally show that rural and urban individuals differ in their fear of humans and in its association with antipredatory and exploratory behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown negative correlations between FID and population trends of bird species in Europe (Møller, ; Díaz et al ., ). Because short FID implies frequent disturbance by humans, individuals that are subject to frequent and increasing numbers of human approaches will experience a higher level of disturbance and an associated negative energy budget that has to be balanced either by emigration to areas with lower human population density (Carrete & Tella, ; Rebolo‐Ifrán et al ., ) or by increased rates of ingestion (Blumstein & Daniel, ).…”
Section: Discussionmentioning
confidence: 99%